Finishing method of chitosan fiber and chitosan fiber prepared by finishing method

By activating chitosan fibers under acidic conditions and combining the dual effects of electrostatic interaction and crosslinking network structure, the problem of poor mechanical properties of chitosan fibers is solved, and a significant improvement in the mechanical properties of fibers and the enhancement of the interaction force of sizing agents is achieved.

CN119686114AActive Publication Date: 2025-03-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411857298.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In the prior art, the mechanical properties of chitosan fibers are poor, and the interaction force between the sizing agent and chitosan fibers is weak, resulting in limited improvement in the mechanical properties of the fibers.

Method used

By activating chitosan fibers under acidic conditions, the surface of the surface electrostatic interaction is used to adsorb anionic polyelectrolytes, and combining pre-crosslinking and heat cross-linking to form a dense cross-linking network structure, improving the mechanical properties of the fibers.

Benefits of technology

It significantly improves the mechanical properties of chitosan fibers, avoids the problem of sizing agent falling off, and has a simple process and low cost, which is suitable for the existing wet spinning process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119686114A_ABST
    Figure CN119686114A_ABST
Patent Text Reader

Abstract

The invention discloses a chitosan fiber finishing method and a prepared chitosan fiber, and the method comprises the following steps: preparing an acidic aqueous solution from an anionic polyelectrolyte, adding a cross-linking agent, uniformly stirring, and carrying out pre-crosslinking to obtain a pre-crosslinked chitosan fiber finishing liquid; and soaking the formed chitosan fiber in the pre-crosslinked chitosan fiber finishing liquid, drying, carrying out thermal crosslinking, and soaking in ethanol to obtain the finished chitosan fiber. By utilizing the property that the chitosan fiber is activated into a cationic electrolyte under an acidic condition, the anionic polyelectrolyte is strongly adsorbed on the surface of the chitosan fiber through electrostatic interaction, so that the problems that the interaction force between a sizing agent and other finishing agents and the chitosan fiber is weak; the problem of poor mechanical property of the chitosan fiber caused by falling of the finishing agent and the sizing agent in the use process is effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile engineering, and in particular relates to a chitosan fiber finishing method and the prepared chitosan fiber. Background Art

[0002] There is a large amount of chitosan in crustaceans such as shrimps and crabs. Chitosan, as a biomass polysaccharide compound, can be obtained through the deacetylation process as a cationic polysaccharide polyelectrolyte, namely chitosan. Chitosan has fiber-forming properties, antibacterial properties, biocompatibility and biodegradability. Chitosan fiber materials can not only be used in the fields of textiles and clothing, but also have a wide range of application prospects in the field of biomedicine. Chitosan can be degraded into harmless products such as glucosamine in the body, so it has great application potential in the fields of surgical sutures, hemostatic materials, wound dressings and regenerative tissue engineering.

[0003] At present, chitosan fibers are prepared by traditional wet spinning process, and the breaking strength ranges from 0.53 to 2.2 cN / dtex. The breaking strength of conventional chitosan fiber products prepared by using dilute acetic acid solution as solvent is 1.07 cN / dtex. The mechanical properties of chitosan fibers are generally poor, which greatly limits their application areas. In order to improve the mechanical properties, blending chitosan fibers with other fibers is the most commonly used and easiest way to improve the mechanical properties of chitosan fibers. However, the presence of blended fibers has a great influence on the biocompatibility of chitosan fibers, especially in the medical field where high requirements are placed on the antibacterial and biocompatibility of materials. There are strong hydrogen bond interactions within and between chitosan molecules, making it difficult to dissolve in general organic solvents.

[0004] In recent years, researchers have conducted a series of studies on the dissolution system of chitosan in order to improve the mechanical properties of chitosan fibers. The dissolution system of chitosan can be summarized into three categories: acid system, ionic liquid system, and alkali / urea system. Chitosan fibers prepared with ionic liquid and alkali / urea system as solvents show higher mechanical strength than chitosan fibers prepared with acetic acid system. However, the synthesis process of ionic liquid and the freeze-thaw cycle process of alkali / urea system are time-consuming, energy-consuming and costly.

[0005] At present, the more mature production process of chitosan fiber mostly uses acetic acid system as solvent. Based on the process of using acetic acid as solvent, researchers chemically cross-linked the prepared chitosan fiber to improve the mechanical properties of chitosan fiber.

[0006] Patent CN 201510182592.8 discloses a medium-temperature textile sizing method, which includes preparing a sizing agent, adding the required clean water into a sizing barrel, starting stirring, adding the obtained dry sizing agent into the sizing barrel, adding ordinary unmodified starch into the sizing barrel, stirring, adding the dry sizing agent again, continuing stirring, and then starting to pass steam for heating. After heating, stop passing steam, keep warm and stir for 30 minutes, pump it into the sizing tank, start the sizing machine, and start sizing. The sizing agent can significantly improve the mechanical properties of the yarn, but due to the weak intermolecular force of the sizing agent, the mechanical properties of the fiber are limited.

[0007] In order to solve the problem of limited fiber mechanical improvement due to weak intermolecular forces between slurries, patent CN201810387628.X discloses a method for preparing chitosan fiber with carboxymethyl chitosan sizing, wherein the chitosan fiber formed by wet spinning is axially stretched in a swelling agent, washed and dried to obtain enhanced chitosan fiber; then, carboxymethyl chitosan is dissolved in water, vacuum degassing is performed to obtain a cross-linked carboxymethyl chitosan sizing agent, and then the enhanced chitosan fiber is immersed in the cross-linked carboxymethyl chitosan sizing agent for uniform sizing and then dried, and finally the sizing enhanced chitosan fiber is immersed in a cross-linking agent solution for cross-linking, and then dried to obtain carboxymethyl chitosan sizing chitosan fiber, whose breaking strength is improved by 88.4 to 114.5% compared with the finished chitosan fiber. Although sizing with a cross-linking sizing agent can increase the mechanical properties of chitosan fiber, the cross-linking process of the current cross-linking modification is before the sizing step, and the slurry concentration increases during the cross-linking process, which is not conducive to subsequent sizing.

[0008] In order to solve the problem that the viscosity of the slurry increases due to the cross-linking reaction before sizing, which leads to the unsmooth fiber sizing process, patent CN 201810385932.0 discloses a method for processing chitosan fiber, wherein the chitosan fiber finished product is axially stretched in a swelling agent, washed and dried to obtain enhanced chitosan fiber, and then the enhanced chitosan fiber is immersed in a sizing agent for uniform sizing and then dried and cross-linked to obtain starch-sizing chitosan fiber, which has a breaking strength increased by 74.8 to 108.1% compared with the chitosan fiber finished product. By introducing a sizing agent and performing a cross-linking reaction, the strength of the chitosan fiber is improved. However, the interaction between the sizing agent and the chitosan fiber is weak, resulting in the mechanical properties of the fiber product being unable to meet the long-term application requirements of the product.

[0009] Therefore, it is of great significance to develop a technology that is low-cost, simple in process, has strong interactions between sizing agents and chitosan fibers and between sizing agents, and is compatible with existing wet spinning processes to improve the mechanical properties of chitosan fibers. Summary of the invention

[0010] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0011] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0012] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for finishing chitosan fibers.

[0013] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for finishing chitosan fibers, comprising:

[0014] The anionic polyelectrolyte is prepared into an acidic aqueous solution, and a cross-linking agent is added and stirred evenly to perform pre-cross-linking to obtain a pre-cross-linked chitosan fiber finishing solution;

[0015] The formed chitosan fiber is immersed in the pre-crosslinked chitosan fiber finishing liquid, dried and thermally crosslinked, and immersed in ethanol to obtain the finished chitosan fiber.

[0016] As a preferred embodiment of the finishing method of the present invention, the shaped chitosan fibers include wet or dry shaped chitosan fibers prepared by wet spinning.

[0017] As a preferred embodiment of the finishing method of the present invention, the chitosan fiber finishing liquid is prepared from the following raw material formula in parts by weight:

[0018] Anionic polyelectrolyte: 1-30 parts;

[0019] Cross-linking agent: 0.4-12 parts;

[0020] Water: 100-300 parts.

[0021] As a preferred embodiment of the finishing method of the present invention, the anionic polyelectrolyte is prepared into an acidic aqueous solution, wherein the acid is selected from one or more of formic acid, acetic acid, adipic acid, citric acid, butanetetracarboxylic acid, p-toluenesulfonic acid, phosphoric acid, sulfuric acid, hydrochloric acid and phytic acid; the anionic polyelectrolyte includes one or more of carboxymethyl cellulose, carboxymethyl dextran, carboxymethyl starch, carboxymethyl chitosan, carboxymethyl cyclodextrin and polyglutamic acid; the cross-linking agent is one or more of ethylene glycol diglycidyl ether, epichlorohydrin, polyethylene glycol glycidyl ether, glyoxal, glutaraldehyde, maleic anhydride and mixed acid anhydride.

[0022] As a preferred embodiment of the finishing method of the present invention, the pre-crosslinking reaction temperature is 30-60° C. and the reaction time is 1-2 hours.

[0023] As a preferred embodiment of the finishing method of the present invention, the shaped chitosan fiber is immersed in the pre-crosslinked chitosan fiber finishing liquid, wherein the immersion time is 1 to 15 minutes.

[0024] As a preferred embodiment of the finishing method of the present invention, the drying heat crosslinking is performed at a temperature of 40 to 80° C. and a drying time of 0.5 to 2 hours.

[0025] As a preferred embodiment of the finishing method of the present invention, the immersion in ethanol is performed for 5 to 20 minutes.

[0026] As a preferred embodiment of the finishing method of the present invention, the pH value of the pre-crosslinked chitosan fiber finishing solution is 5.5-6.5.

[0027] Another object of the present invention is to overcome the deficiencies in the prior art and provide a chitosan fiber prepared by a chitosan fiber finishing method.

[0028] Beneficial effects of the present invention:

[0029] (1) The present invention utilizes the property of chitosan fiber to be activated into a cationic electrolyte under acidic conditions, and strongly adsorbs anionic polyelectrolytes on its surface through electrostatic interaction, thereby effectively solving the problem of weak interaction between sizing agents and other finishing agents and chitosan fibers, and effectively avoiding the problem of poor mechanical properties of chitosan fibers caused by the shedding of finishing agents and sizing agents during use.

[0030] (2) The present invention cross-links and modifies the fibers by combining pre-crosslinking and thermal crosslinking, so that the cross-linked network structure formed by the anionic electrolyte adsorbed on the surface of the chitosan fiber is denser and stronger, which greatly enhances the interaction between the molecular chains and effectively improves the mechanical properties of the chitosan fiber.

[0031] (3) The present invention forms a dense cross-linked network structure on the fiber surface through the dual effects of electrostatic interaction and chemical cross-linking, thereby improving the mechanical strength of the chitosan fiber and achieving the purpose of fiber surface modification; the entire process is simple, low in energy consumption, low in cost, and can be implemented in the existing chitosan wet spinning finishing process. The finished chitosan fiber has a wide range of uses and can be used for medical sutures, medical wound dressings, medical tissue engineering, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0033] Figure 1 This is a physical picture of the chitosan fiber obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0037] Mechanism of the invention:

[0038] The present invention soaks wet or dry chitosan fibers in an acidic finishing solution containing anionic polyelectrolytes. In the acidic finishing solution, a large number of amino groups on the molecular chains of the chitosan fibers are activated and combined with ionized hydrogen ions in the acidic finishing solution to convert the chitosan fibers into cationic polyelectrolytes, destroying the hydrogen bond structure of the fiber surface, causing the molecular chains to be untangled to a certain extent, and forming a swollen body with positive charges on the fiber surface.

[0039] Chitosan fibers with positive charge can form polyelectrolyte complexes when they encounter anionic polyelectrolytes in the finishing solution.

[0040] The finishing agent used in the present invention is an anionic polyelectrolyte that can interact electrostatically with chitosan fibers. The electrostatic interaction between activated chitosan fibers and anionic polyelectrolytes is utilized to strengthen the adhesion between the sizing agent or finishing liquid and the chitosan fibers, thus solving the problem of no interaction between the sizing agent and the chitosan fibers in the prior art.

[0041] The anionic polyelectrolyte undergoes a pre-crosslinking reaction in an acidic solution containing a crosslinking agent to form a certain weak crosslinking network. The weak crosslinking network with negative charge is adsorbed on the surface of the chitosan fiber through electrostatic interaction under acidic conditions. During the drying process, the fibers adsorbed on the surface of the chitosan fiber are further thermally crosslinked to form a denser crosslinking network structure. The crosslinked network structure is beneficial to improving the mechanical properties of the fiber and can firmly bind the polyelectrolyte complex to the fiber surface.

[0042] The present invention is the first to modify the fiber by combining pre-crosslinking and thermal crosslinking. Pre-crosslinking can ensure that the crosslinking reaction occurs in a liquid environment without causing the sizing agent to be too viscous, making it difficult to sizing. At the same time, thermal crosslinking in the subsequent fiber drying process further promotes the occurrence of the crosslinking reaction, prompting the crosslinking network to form completely, strengthening the intermolecular force, and improving the fiber strength.

[0043] The dual effects of the electrostatic interaction between chitosan fiber and anionic polyelectrolyte and the cross-linked network structure of anionic polyelectrolyte on the fiber surface significantly improve the mechanical properties of chitosan fiber and avoid the problem of the mechanical properties of chitosan fiber being affected by the shedding of slurry during use.

[0044] The experimental materials used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent companies, and carboxymethyl cellulose (molecular weight 90,000) was purchased from the Aladdin Chemical Reagent website.

[0045] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:

[0046] (1) Mechanical properties (including breaking strength and breaking elongation) were measured by a universal tensile testing machine (referring to the national standard GB / T 14344).

[0047] (2) The fracture strength improvement rate is calculated by the following formula:

[0048]

[0049] In the formula, the breaking strength (after finishing) refers to the breaking strength of the chitosan fiber after finishing with the technology of the present invention; the breaking strength (before finishing) refers to the breaking strength of the chitosan fiber before finishing with the technology of the present invention.

[0050] (3) The elongation at break increase rate is calculated by the following formula:

[0051]

[0052] In the formula, the elongation at break (after finishing) refers to the elongation at break of the chitosan fiber after finishing by the technology of the present invention; the elongation at break (before finishing) refers to the elongation at break of the chitosan fiber before finishing by the technology of the present invention.

[0053] (4) The chitosan fibers and related experimental raw materials used in the following examples are obtained by the following preparation method:

[0054] Prepare acetic acid into a dilute acetic acid solution with a volume fraction of 2%;

[0055] Slowly adding chitosan powder into the dilute acetic acid solution to prepare a chitosan spinning solution with a mass fraction of 4wt%, and forming a uniform and stable chitosan solution after vacuum degassing;

[0056] The chitosan spinning solution is injected into a sodium hydroxide / ethanol aqueous solution for wet spinning, and a portion of the formed chitosan fibers are washed without drying to obtain wet chitosan fibers;

[0057] A portion of the formed chitosan fibers are dried in an oven to obtain dry chitosan fibers.

[0058] Example 1

[0059] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0060] Anionic polyelectrolyte (carboxymethyl cellulose): 30 parts;

[0061] Cross-linking agent (ethylene glycol diglycidyl ether): 12 parts;

[0062] Water: 300 parts;

[0063] 30 parts of anionic polyelectrolyte (carboxymethyl cellulose) and 12 parts of crosslinking agent (ethylene glycol diglycidyl ether) were slowly added to 300 parts of deionized water solution, and then formic acid was added to adjust the pH value of the solution to 5.5, and the solution was fully stirred, and the solution was placed at 60°C for 1 hour to obtain a pre-crosslinked chitosan fiber finishing solution;

[0064] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 10 minutes, the fiber with the finishing liquid was taken out and placed in a 60°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 5 minutes to obtain the finished chitosan fiber.

[0065] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 113.8%, and the breaking elongation was increased by 23.8% compared with the chitosan fiber finished product.

[0066] The test results are shown in Table 1.

[0067] Example 2

[0068] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0069] Anionic polyelectrolyte (carboxymethyl cyclodextrin): 5 parts;

[0070] Cross-linking agent (ethylene glycol diglycidyl ether): 1 part;

[0071] Water: 200 parts;

[0072] Slowly add 5 parts of anionic polyelectrolyte (carboxymethyl cyclodextrin) and 1 part of crosslinking agent (ethylene glycol diglycidyl ether) into 200 parts of deionized water solution, and then add acetic acid to adjust the pH value of the solution to 6.4, stir well, and place the solution at 30°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0073] The dried chitosan fiber was immersed in the above fiber finishing liquid for 15 minutes at room temperature, the fiber with finishing liquid was taken out and placed in an oven at 80℃ for thermal crosslinking reaction for 0.5 hours, and the dried chitosan fiber was immersed in ethanol for 8 minutes to obtain the finished chitosan fiber. The performance of the crosslinked chitosan fiber was tested, and the final crosslinked chitosan fiber had a 104.1% higher breaking strength and a 21.3% higher breaking elongation than the finished chitosan fiber.

[0074] The test results are shown in Table 1.

[0075] Example 3

[0076] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0077] Anionic polyelectrolyte (carboxymethyl starch): 18 parts;

[0078] Cross-linking agent (ethylene glycol diglycidyl ether): 10 parts;

[0079] Water: 300 parts;

[0080] 18 parts of anionic polyelectrolyte (carboxymethyl starch) and 10 parts of crosslinking agent (ethylene glycol diglycidyl ether) were slowly added to 300 parts of deionized water solution, and then adipic acid was added to adjust the pH value of the solution to 6.1, and the solution was fully stirred, and the solution was placed at 60°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0081] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 10 minutes, the fiber with the finishing liquid was taken out and placed in a 40°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 6 minutes to obtain the finished chitosan fiber.

[0082] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 105.4%, and the breaking elongation was increased by 20.5% compared with the finished chitosan fiber.

[0083] The test results are shown in Table 1.

[0084] Example 4

[0085] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0086] Anionic polyelectrolyte (polyglutamic acid): 20 parts;

[0087] Cross-linking agent (ethylene glycol diglycidyl ether): 8 parts;

[0088] Water: 200 parts;

[0089] Slowly add 20 parts of anionic polyelectrolyte (polyglutamic acid) and 8 parts of cross-linking agent (ethylene glycol diglycidyl ether) into 200 parts of deionized water solution, and then add acetic acid to adjust the pH value of the solution to 6.0, stir thoroughly, and place the above solution at 50°C for reaction for 2 hours to obtain a pre-cross-linked chitosan fiber finishing solution; immerse the dried chitosan fiber in the above fiber finishing solution and soak it at room temperature for 12 minutes, take out the fiber with the finishing solution and place it in a 70°C oven for thermal cross-linking reaction for 2 hours, and immerse the dried chitosan fiber in ethanol for 7 minutes to obtain the finished chitosan fiber.

[0090] The performance of the cross-linked chitosan fiber was tested, and the results showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 121.2%, and the breaking elongation was increased by 25.8% compared with the chitosan fiber finished product.

[0091] The test results are shown in Table 1. Figure 1 .

[0092] Example 5

[0093] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0094] Anionic polyelectrolyte (carboxymethyl dextran): 15 parts;

[0095] Cross-linking agent (epichlorohydrin): 5 parts;

[0096] Water: 200 parts;

[0097] 15 parts of anionic polyelectrolyte (carboxymethyl dextran) and 5 parts of crosslinking agent (epichlorohydrin) were slowly added to 200 parts of deionized water solution, and then citric acid was added to adjust the pH value of the solution to 5.7, and the solution was fully stirred, and the solution was placed at 50°C for 1.25 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0098] The dried chitosan fiber was immersed in the above fiber finishing liquid for 12 minutes at room temperature, the fiber with finishing liquid was taken out and placed in a 60℃ oven for thermal crosslinking reaction for 1.5 hours, and the dried chitosan fiber was immersed in ethanol for 6 minutes to obtain the finished chitosan fiber. The performance of the crosslinked chitosan fiber was tested, and the final crosslinked chitosan fiber had a 109.4% higher breaking strength and a 21.4% higher breaking elongation than the finished chitosan fiber.

[0099] The test results are shown in Table 1.

[0100] Example 6

[0101] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0102] Anionic polyelectrolyte (carboxymethyl cellulose): 10 parts;

[0103] Cross-linking agent (maleic anhydride): 2 parts;

[0104] Water: 100 parts;

[0105] 10 parts of anionic polyelectrolyte (carboxymethyl cellulose) and 2 parts of crosslinking agent (maleic anhydride) were slowly added to 100 parts of deionized water solution, and then citric acid was added to adjust the pH value of the solution to 5.5, and the solution was fully stirred, and the solution was placed at 40°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0106] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 14 minutes, the fiber with the finishing liquid was taken out and placed in a 50°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 8 minutes to obtain the finished chitosan fiber.

[0107] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 118.5%, and the breaking elongation was increased by 20.8% compared with the finished chitosan fiber.

[0108] The test results are shown in Table 1.

[0109] Example 7

[0110] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0111] Anionic polyelectrolyte (polyglutamic acid): 15 parts;

[0112] Cross-linking agent (maleic anhydride): 9 parts;

[0113] Water: 250 parts;

[0114] 15 parts of anionic polyelectrolyte (polyglutamic acid) and 9 parts of cross-linking agent (maleic anhydride) are slowly added to 250 parts of deionized water solution, and then hydrochloric acid is added to adjust the pH value of the solution to 5.8, and the solution is fully stirred. The above solution is placed at 30°C for reaction for 1 hour to obtain a pre-cross-linked chitosan fiber finishing solution; the dried chitosan fiber is immersed in the above fiber finishing solution and soaked at room temperature for 11 minutes. The fiber with the finishing solution is taken out and placed in a 65°C oven for thermal cross-linking reaction for 2 hours. The dried chitosan fiber is immersed in ethanol for 9 minutes to obtain the finished chitosan fiber.

[0115] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 103.2%, and the breaking elongation was increased by 21.3% compared with the finished chitosan fiber.

[0116] The test results are shown in Table 1.

[0117] Example 8

[0118] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0119] Anionic polyelectrolyte (polyglutamic acid): 30 parts;

[0120] Cross-linking agent (maleic anhydride): 10 parts;

[0121] Water: 300 parts;

[0122] 30 parts of anionic polyelectrolyte (polyglutamic acid) and 10 parts of crosslinking agent (maleic anhydride) were slowly added to 300 parts of deionized water solution, and then sulfuric acid was added to adjust the pH value of the solution to 5.6, and the solution was fully stirred, and the solution was placed at 30°C for 1.75 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0123] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 13 minutes, the fiber with the finishing liquid was taken out and placed in a 75°C oven for thermal crosslinking reaction for 1.5 hours, and the dried chitosan fiber was immersed in ethanol for 10 minutes to obtain the finished chitosan fiber.

[0124] The performance of the cross-linked chitosan fiber was tested, and the results showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 115.4%, and the breaking elongation was increased by 24.6% compared with the chitosan fiber finished product.

[0125] The test results are shown in Table 1.

[0126] Example 9

[0127] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0128] Anionic polyelectrolyte (carboxymethyl chitosan): 20 parts;

[0129] Cross-linking agent (glutaraldehyde): 10 parts;

[0130] Water: 250 parts;

[0131] 20 parts of anionic polyelectrolyte (carboxymethyl chitosan) and 10 parts of crosslinking agent (glutaraldehyde) were slowly added to 250 parts of deionized water solution, and then phosphoric acid was added to adjust the pH value of the solution to 5.5, and the solution was fully stirred, and the solution was placed at 55°C for 1 hour to obtain a pre-crosslinked chitosan fiber finishing solution;

[0132] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 11 minutes, the fiber with the finishing liquid was taken out and placed in a 70°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 10 minutes to obtain the finished chitosan fiber.

[0133] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 120.2%, and the breaking elongation was increased by 20.4% compared with the finished chitosan fiber.

[0134] The test results are shown in Table 1.

[0135] Example 10

[0136] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0137] Anionic polyelectrolyte (carboxymethyl dextran): 1 part;

[0138] Cross-linking agent (mixed anhydride): 0.4 parts;

[0139] Water: 100 parts;

[0140] 1 part of anionic polyelectrolyte (carboxymethyl dextran) and 0.4 part of crosslinking agent (mixed anhydride) were slowly added to 100 parts of deionized water solution, and then p-toluenesulfonic acid was added to adjust the pH value of the solution to 5.7, and the solution was stirred thoroughly, and the solution was placed at 60°C for 1.5 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0141] The wet chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 3 minutes, the fiber with the finishing liquid was taken out and placed in an oven at 80°C for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 12 minutes to obtain the finished chitosan fiber.

[0142] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 102.4%, and the breaking elongation was increased by 24.5% compared with the chitosan fiber finished product.

[0143] The test results are shown in Table 1.

[0144] Embodiment 11

[0145] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0146] Anionic polyelectrolyte (carboxymethyl dextran): 10 parts;

[0147] Cross-linking agent (maleic anhydride): 4 parts;

[0148] Water: 300 parts;

[0149] 10 parts of anionic polyelectrolyte (carboxymethyl dextran) and 4 parts of crosslinking agent (maleic anhydride) were slowly added to 300 parts of deionized water solution, and then phytic acid was added to adjust the pH value of the solution to 5.6, and the solution was fully stirred, and the solution was placed at 40°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0150] The wet chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 2 minutes, the fiber with the finishing liquid was taken out and placed in an oven at 80°C for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 13 minutes to obtain the finished chitosan fiber.

[0151] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 99.6% and the breaking elongation was increased by 23.6% compared with the finished chitosan fiber.

[0152] The test results are shown in Table 1.

[0153] Example 12

[0154] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0155] Anionic polyelectrolyte (carboxymethyl cellulose): 1 part;

[0156] Cross-linking agent (glyoxal): 0.6 parts;

[0157] Water: 150 parts;

[0158] 1 part of anionic polyelectrolyte (carboxymethyl cellulose) and 0.6 part of crosslinking agent (glyoxal) were slowly added to 150 parts of deionized water solution, and then butane tetracarboxylic acid was added to adjust the solution pH to 6.4, and the solution was stirred thoroughly, and the solution was placed at 60°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0159] The wet chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 5 minutes, the fiber with the finishing liquid was taken out and placed in an oven at 80°C for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 15 minutes to obtain the finished chitosan fiber.

[0160] The performance of the cross-linked chitosan fiber was tested, and the result showed that the breaking strength of the cross-linked chitosan fiber finally prepared was increased by 92.4% and the breaking elongation was increased by 22.2% compared with the finished chitosan fiber.

[0161] The test results are shown in Table 1.

[0162] Example 13

[0163] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0164] Anionic polyelectrolyte (polyglutamic acid): 12 parts;

[0165] Cross-linking agent (polyethylene glycol glycidyl ether): 5 parts;

[0166] Water: 150 parts;

[0167] 12 parts of anionic polyelectrolyte (polyglutamic acid) and 5 parts of crosslinking agent (polyethylene glycol glycidyl ether) were slowly added to 150 parts of deionized water solution, and then acetic acid was added to adjust the pH value of the solution to 6.2, and the solution was stirred thoroughly, and the solution was placed at 60°C for 1.5 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0168] The wet chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 1 minute, the fiber with the finishing liquid was taken out and placed in an oven at 80°C for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 14 minutes to obtain the finished chitosan fiber.

[0169] The performance of the cross-linked chitosan fiber was tested, and the breaking strength of the cross-linked chitosan fiber finally obtained was increased by 91.5% and the breaking elongation was increased by 20.7% compared with the chitosan fiber finished product. The test results are shown in Table 1.

[0170] Comparative Example 1

[0171] The method of Example 4 is followed, except that no crosslinking agent is added. If no crosslinking agent is added, there is no subsequent crosslinking reaction, and the polyanion polyelectrolyte is only adsorbed onto the chitosan fiber by electrostatic force, and the obtained chitosan fiber is tested.

[0172] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0173] Anionic polyelectrolyte (polyglutamic acid): 20 parts;

[0174] Water: 200 parts;

[0175] Slowly add 20 parts of anionic polyelectrolyte (polyglutamic acid) to 200 parts of deionized water solution, then add acetic acid to adjust the pH value of the solution to 6.0, stir thoroughly, and place the solution at 50°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0176] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 12 minutes, the fiber with the finishing liquid was taken out and placed in a 70°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 5 minutes to obtain the finished chitosan fiber.

[0177] The performance of the cross-linked chitosan fiber was tested, and the breaking strength of the cross-linked chitosan fiber finally obtained was 2.3% higher than that of the chitosan fiber finished product, and the breaking elongation was 0.9%. The test results are shown in Table 1.

[0178] Comparative Example 2

[0179] The chitosan fibers obtained were tested according to the method of Example 4 except that no pre-crosslinking was performed.

[0180] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0181] Anionic polyelectrolyte (polyglutamic acid): 20 parts;

[0182] Cross-linking agent (ethylene glycol diglycidyl ether): 8 parts;

[0183] Water: 200 parts;

[0184] 20 parts of anionic polyelectrolyte (polyglutamic acid) and 8 parts of cross-linking agent (ethylene glycol diglycidyl ether) were slowly added to 200 parts of deionized water solution, and then acetic acid was added to adjust the pH value of the solution to 6.0. After sufficient stirring, the dried chitosan fiber was immersed in the above fiber finishing solution and soaked at room temperature for 12 minutes. The fiber with the finishing solution was taken out and placed in a 70°C oven for thermal cross-linking reaction for 2 hours. The dried chitosan fiber was immersed in ethanol for 5 minutes to obtain the finished chitosan fiber.

[0185] The performance of the cross-linked chitosan fiber was tested, and the breaking strength of the cross-linked chitosan fiber finally obtained was 1.3% higher than that of the chitosan fiber finished product, and the breaking elongation was 1.1%. The test results are shown in Table 1.

[0186] Comparative Example 3

[0187] The method of Example 4 was followed, except that no acid was added to adjust the pH value of the finishing solution. The obtained chitosan fibers were tested.

[0188] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0189] Anionic polyelectrolyte (polyglutamic acid): 20 parts;

[0190] Cross-linking agent (ethylene glycol diglycidyl ether): 8 parts;

[0191] Water: 200 parts;

[0192] Slowly add 20 parts of anionic polyelectrolyte (polyglutamic acid) and 8 parts of crosslinking agent (ethylene glycol diglycidyl ether) into 200 parts of deionized water solution, stir thoroughly, and place the solution at 50°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0193] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 12 minutes, the fiber with the finishing liquid was taken out and placed in a 70°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 6 minutes to obtain the finished chitosan fiber.

[0194] The performance of the cross-linked chitosan fiber was tested. The results showed that the breaking strength of the cross-linked chitosan fiber finally prepared was 3.1% higher than that of the finished chitosan fiber, and the breaking elongation was 1.5%.

[0195] The test results are shown in Table 1.

[0196] Comparative Example 4

[0197] The method of Example 4 was followed, except that the thermal cross-linking process was not performed. The obtained chitosan fibers were tested.

[0198] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0199] Anionic polyelectrolyte (polyglutamic acid): 20 parts;

[0200] Cross-linking agent (ethylene glycol diglycidyl ether): 8 parts;

[0201] Water: 200 parts;

[0202] 20 parts of anionic polyelectrolyte (polyglutamic acid) and 8 parts of crosslinking agent (ethylene glycol diglycidyl ether) were slowly added to 200 parts of deionized water solution, and then acetic acid was added to adjust the pH value of the solution to 6.0, and the solution was stirred thoroughly, and the solution was placed at 50°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0203] The dried chitosan fibers were immersed in the above fiber finishing solution at room temperature for 12 minutes, the fibers with the finishing solution were taken out and dried at room temperature without drying, and the dried chitosan fibers were immersed in ethanol for 6 minutes to obtain the finished chitosan fibers.

[0204] The performance of the cross-linked chitosan fiber was tested, and the breaking strength of the cross-linked chitosan fiber finally obtained was 4.2% higher than that of the chitosan fiber finished product, and the breaking elongation was 2.5%. The test results are shown in Table 1.

[0205] Comparative Example 5

[0206] The method of Example 4 is followed, except that no cross-linking agent is added, but the amount of anionic polyelectrolyte added is equal to the total amount of anionic polyelectrolyte and cross-linking agent.

[0207] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0208] Anionic polyelectrolyte (polyglutamic acid): 28 parts;

[0209] Water: 200 parts;

[0210] 28 parts of anionic polyelectrolyte (polyglutamic acid) were slowly added to 200 parts of deionized water solution, and then acetic acid was added to adjust the pH value of the solution to 6.0, and the solution was stirred thoroughly, and the solution was placed at 50°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0211] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 12 minutes, the fiber with the finishing liquid was taken out and placed in a 70°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 5 minutes to obtain the finished chitosan fiber.

[0212] See Table 1 for the results.

[0213] Comparative Example 6

[0214] The method of Example 4 is followed, except that no anionic polyelectrolyte is added, but the amount of anionic polyelectrolyte added is equivalent to the total amount of anionic polyelectrolyte and cross-linking agent.

[0215] Preparation of finishing liquid: weigh the following raw material formula in parts by weight to prepare chitosan fiber finishing liquid:

[0216] Cross-linking agent (ethylene glycol diglycidyl ether): 28 parts;

[0217] Water: 200 parts;

[0218] Slowly add 28 parts of ethylene glycol diglycidyl ether to 200 parts of deionized water, then add acetic acid to adjust the pH value of the solution to 6.0, stir thoroughly, and place the solution at 50°C for 2 hours to obtain a pre-crosslinked chitosan fiber finishing solution;

[0219] The dried chitosan fiber was immersed in the above fiber finishing liquid at room temperature for 12 minutes, the fiber with the finishing liquid was taken out and placed in a 70°C oven for thermal crosslinking reaction for 2 hours, and the dried chitosan fiber was immersed in ethanol for 5 minutes to obtain the finished chitosan fiber.

[0220] See Table 1 for the results.

[0221] Table 1

[0222] Breaking strength improvement rate (%) Elongation at break increase rate (%) Example 1 113.8 23.8 Example 2 104.1 21.3 Example 3 105.4 20.5 Example 4 121.2 25.8 Example 5 109.4 21.4 Example 6 118.5 20.8 Example 7 103.2 21.3 Example 8 115.4 24.6 Example 9 120.2 20.4 Example 10 102.4 24.5 Embodiment 11 99.6 23.6 Example 12 92.4 22.0 Example 13 91.5 20.7 Comparative Example 1 2.3 0.9 Comparative Example 2 1.3 1.1 Comparative Example 3 3.1 1.5 Comparative Example 4 4.2 2.5 Comparative Example 5 1.2 1.1 Comparative Example 6 0.3 1.2

[0223] As can be seen from Table 1, the present invention adopts a combination of pre-crosslinking and thermal crosslinking to modify the fiber. Pre-crosslinking can ensure that the crosslinking reaction occurs in a liquid environment, and will not cause the sizing agent to be too viscous, resulting in difficulty in sizing. At the same time, thermal crosslinking in the subsequent fiber drying process further promotes the occurrence of the crosslinking reaction, prompting the crosslinking network to form completely, enhancing the intermolecular force, and improving the fiber strength. The dual effects of the electrostatic interaction between the chitosan fiber and the anionic polyelectrolyte and the crosslinked network structure of the anionic polyelectrolyte on the fiber surface significantly improve the mechanical properties of the chitosan fiber, avoiding the problem of affecting the mechanical properties of the chitosan fiber due to the shedding of the slurry during use. At the same time, it can be seen from the comparative examples that there is a synergistic effect between the anionic polyelectrolyte and the crosslinking agent, which jointly improves the mechanical properties of the chitosan fiber.

[0224] The purpose of the present invention is to provide a method with simple process, low production cost and the ability to improve the mechanical strength of chitosan fiber in view of the problems of poor mechanical properties of chitosan fiber, weak interaction between sizing agent and chitosan fiber, and weak interaction between sizing agents in the existing chitosan fiber cross-linking modification technology. In the prior art, the cross-linking process occurs before sizing, and the viscosity of the sizing agent is too large, which makes the sizing process difficult and there is no interaction between the sizing agent and the chitosan fiber, which easily causes the sizing agent to fall off. In the prior art, the cross-linking process occurs after sizing. Since the cross-linking process needs to be carried out in a liquid environment, that is, the cross-linking process occurs during the fiber drying process, the liquid evaporates quickly, resulting in incomplete cross-linking reaction, incomplete formation of the cross-linking network, weak intermolecular force, and poor fiber strength. Chitosan, as the only natural cationic polysaccharide polyelectrolyte in nature, can form a cationic polyelectrolyte with dissociated hydrogen ions under acidic conditions, and it can interact with anionic polyelectrolytes to form polyelectrolyte complexes. Electrostatic interaction can adsorb the pre-cross-linked anionic polyelectrolyte to obtain the surface of chitosan fiber, thereby enhancing the interaction between chitosan fiber and the finishing agent. The anionic polyelectrolytes adsorbed on the surface of chitosan fibers are further thermally cross-linked and cured under the action of the cross-linking agent to form a dense cross-linked network structure, which enhances the interaction between molecular chains and improves the mechanical strength of chitosan fibers. The anionic polyelectrolytes on the surface of chitosan greatly improve the mechanical properties of chitosan fibers through the dual effects of electrostatic interaction and cross-linked network structure.

[0225] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for finishing chitosan fibers, characterized in that: include, The anionic polyelectrolyte is prepared into an acidic aqueous solution, and a cross-linking agent is added and stirred evenly to perform pre-cross-linking to obtain a pre-cross-linked chitosan fiber finishing solution; The formed chitosan fiber is immersed in the pre-crosslinked chitosan fiber finishing liquid, dried and thermally crosslinked, and immersed in ethanol to obtain the finished chitosan fiber.

2. The finishing method according to claim 1, characterized in that: The shaped chitosan fiber includes wet or dry shaped chitosan fiber prepared by wet spinning.

3. The finishing method according to claim 1 or 2, characterized in that: The chitosan fiber finishing liquid is prepared from the following raw material formula in parts by weight: Anionic polyelectrolyte: 1-30 parts; Cross-linking agent: 0.4-12 parts; Water: 100-300 parts.

4. The finishing method according to claim 3, characterized in that: The anionic polyelectrolyte is prepared into an acidic aqueous solution, wherein the acid is selected from one or more of formic acid, acetic acid, adipic acid, citric acid, butanetetracarboxylic acid, p-toluenesulfonic acid, phosphoric acid, sulfuric acid, hydrochloric acid and phytic acid; The anionic polyelectrolyte comprises one or more of carboxymethyl cellulose, carboxymethyl dextran, carboxymethyl starch, carboxymethyl chitosan, carboxymethyl cyclodextrin and polyglutamic acid; The cross-linking agent is one or more of ethylene glycol diglycidyl ether, epichlorohydrin, polyethylene glycol glycidyl ether, glyoxal, glutaraldehyde, maleic anhydride, and mixed anhydride.

5. The finishing method according to claim 4, characterized in that: The pre-crosslinking reaction temperature is 30-60° C. and the reaction time is 1-2 hours.

6. The finishing method according to claim 5, characterized in that: The formed chitosan fiber is immersed in the pre-crosslinked chitosan fiber finishing liquid, wherein the immersion time is 1 to 15 minutes.

7. The finishing method according to claim 6, characterized in that: The drying heat crosslinking, wherein the drying temperature is 40-80° C., and the time is 0.5-2 h.

8. The finishing method according to claim 7, characterized in that: The immersion in ethanol, wherein the immersion time is 5 to 20 minutes.

9. The finishing method according to any one of claims 1, 2, 4 to 8, characterized in that: The pH value of the pre-crosslinked chitosan fiber finishing liquid is 5.5-6.

5.

10. Chitosan fiber obtained by the finishing method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A kind of middle temperature textile sizing method

    CN104790211B

  • Treatment method for chitosan fibers

    CN108625172A

  • A method for preparing carboxymethyl chitosan sized chitosan fibers

    CN108729225B

  • Preparation method of high-strength medical suture thread

    CN108660737A